Analysis of high-temperature performance of polymer-modified asphalts through molecular dynamics simulations and experiments. (3rd October 2022) - Lu, Pengzhen; Ma, Yiheng; Ye, Kai; Huang, Simin
Highlights: Propose a new polymer-modified asphalt using method of molecular dynamics. Analyzed the solubility parameters and interaction energy calculated. Evaluate the compatibility index of polymer-modified asphalt. Compared and analyzed the temperature sensitivity and high temperature properties. Provided a new idea and direction of high-performance asphalt pavement. Abstract: The low durability of asphalt pavements is a key problem limiting successful highway operation and construction; the high-temperature stability of asphalt is an important factor affecting asphalt-pavement durability. To improve the thermal stability of base asphalt, a new polymer-modified asphalt is developed by using polyurethane (PU) as a modifier. Moreover, dynamic research is conducted on the microscopic and mechanical properties of asphalt through molecular dynamics simulations, and the high-temperature performance of the new polymer-modified asphalt is comprehensively evaluated and analyzed through micro- and macro-tests. First, through molecular dynamics and using the three-dimensional materials science simulation software, an asphalt molecular model, a PU molecular model, and an asphalt PU Blend System model are constructed and the correctness of the models is verified. Second, the compatibility index of polymer-modified asphalt is evaluated using solubility parameters and interaction energies calculated in the simulation. Finally, the temperature sensitivity and high-temperature properties of Matrix502-modified asphalt and polymer-modified asphalt are compared and analyzed by using the Brookfield viscosity method and through thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results show that the self-made new polymer-modified asphalt exhibits good thermal storage stability and good high-temperature stability. In addition, a dynamic study on the microcosmic and mechanical properties of the molecules in the asphalt system is conducted through molecular dynamics simulations, and comprehensive evaluation and analysis of the asphalt performance are performed in combination with the microscopic and macroscopic tests. This study promote the research and development of high-performance materials for asphalt pavements.